Soviet-Hungarian relationships on the threshold of the great patriotic war - Valeryi Alekseevich Letyaev, Yakov Yakovlevich Grishin, Vyacheslav Aleksandrovich Shagalov; Yulia Sergeevna Manina, Sharafutdinov (Opción, 2019)
The study aims to investigate Soviet-Hungarian relationships on the threshold of the Great Patriotic War via reconstruction historical document-based methods, a history-and-genetics method, comparative-and-historical method and analysis and synthesis method. As a result, the details of negotiations between the USSR and Hungary in Budapest and Moscow are discovered; the role of politicians such as Molotov, Krishtoffi, Sharonov, Chaki, Vyshinsky is shown. In conclusion, within the period under our consideration, as the documents bear witness, the Soviet Union in its relationships with Hungary followed the principles of peace-policy and kind neighborhood, holding to the basic points of diplomacy.